THE CONCEPT OF THE CRIME OF MONEY LAUNDERING AND ITS SPECIFIC FEATURES - Nazarov Shavkat Nazarovich (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the legal concept and specific characteristics of money laundering within the context of Uzbekistan, while proposing improvements to criminal law and preventive mechanisms. Method: A qualitative doctrinal and comparative legal approach is employed, analyzing Article 243 of the Criminal Code of Uzbekistan, international conventions, and scholarly perspectives. Results: The study finds that money laundering involves disguising the origin of illicit assets through transactions such as transfer, exchange, or concealment, and is primarily facilitated by organized criminal groups. It also establishes that defining money laundering exclusively in terms of monetary funds restricts legal enforcement and undermines investigative processes. Novelty: The research contributes to the academic discourse by advocating for a broader legal definition that encompasses all forms of property and highlights the intricate relationship between money laundering and predicate crimes. This broader conceptualization addresses gaps in current legislation and enhances both legal clarity and prosecutorial effectiveness. Strengthening institutional frameworks and aligning national practices with international standards are essential for advancing economic integrity and national security.